Fighting identity theft! : how to protect your personal finances - Warren, Carolyn, 1950- (FT Press Delivers elements., 2010)
"This Element is an excerpt from Homebuyers beware: who's ripping you off now?--what you must know about the new rules of mortgage and credit (ISBN: 9780137020164) by Carolyn Warren. Ten powerful new ways to prevent or respond to identity theft--techniques you haven't already heard!"--Resource description page.